ANALISIS FINANSIAL DAN NILAI TAMBAH AGROINDUSTRI KERIPIK PISANG SKALA UMK DI KOTA METRO - Febriyanti Febriyanti; Muhammad Irfan Affandi; Umi Kalsum (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2017)
This study aims to analyze  financial feasibility and added value of banana chip agroindustries. This research was conducted in  five districts in Metro City. This research used a census method. Total respondents were twelve agro-industries that produce banana chips. The analysis tool used in this research were financial analysis and the analysis of value-added Hayami model. The results showed that the banana chip agro-industries in Metro City both micro and small scale industries were  financially feasible. The NPVs of micro scale agroindustry were Rp61,724,706.80 – Rp545,335,264.28, IRR values 44.82 - 72.84 percent and  payback periods from 1 year and 2 months 5 days to 4 years 4 months and 3 days.  As for small  scale agroindustry, NPVs were Rp633,256,802.33 – Rp817,129,687.43 , IRR values 45.85 - 56.12 percent, and  payback periods  from 2 years 0 months 6 days - 6 years 3 months and 3 day.Key words: added value, banana chip agroindustry,  financial analysis